Pathological changes, distribution and detection of Brucella melitensis in foetuses of experimentally- infected does - Mazlan, Mazlina; Bejo, Siti Khairani; Hamzah, Hazilawati; Nasruddin, Nurrul Shaqinah; Salleh, Annas; Saad, Mohd Zamri (Taylor & Francis, 2021)
Background: Brucellosis of goats is caused by Brucella melitensis. It is a re-emerging zoonotic disease in many countries due to transmission from domestic animals and wildlife such as ibex, deer and wild buffaloes. Objective: To describe the pathological changes, identification and distribution of B. melitensis in foetuses of experimentally infected does. Methods: Twelve female goats of approximately 90 days pregnant were divided into 4 groups. Group 1 was exposed intra-conjunctival to 100 mL of sterile PBS while goats of Groups 2, 3 and 4 were similarly exposed to 100 mL of an inoculum containing 109 CFU/mL of live B. melitensis. Goats of these groups were killed at 15, 30 and 60 days post-inoculation, respectively. Foetal fluid and tissues were collected for bacterial identification (using direct bacterial culture, PCR and immuno-peroxidase staining) and histopathological examination. Results: Bilateral intra-conjunctival exposure of pregnant does resulted in in-utero infection of the foetuses. All full-term foetuses of group 4 were either aborted or stillborn, showing petechiations of the skin or absence of hair coat with subcutaneous oedema. The internal organs showed most severe lesions. Immune-peroxidase staining revealed antigen distribution in all organs that became most extensive in group 4. Brucella melitensis was successfully isolated from the stomach content, foetal fluid and various other organs. Conclusion: Vertical transmission of caprine brucellosis was evident causing mild to moderate lesions in different organs. The samples of choice for isolation and identification of B. melitensis are stomach content as well as liver and spleen tissue.